A Focus Group Study about Oral Drug Administration Practices at Hospital Wards-Aspects to Consider in Drug Development of Age-Appropriate Formulations for Children - Maria Rautamo; Kirsi Kvarnström; Mia Sivén; Marja Airaksinen; Pekka Lahdenne; Niklas Sandler (MDPI AG, 2020)
Oral drug administration to pediatric patients is characterized by a lack of age-appropriate drug products and the off-label use of medicines. However, drug administration practices at hospital wards is a scarcely studied subject. The aim of this study was to explore the oral drug administration practices at pediatric hospital wards, with a focus on experiences and challenges faced, methods used to mitigate existing problems, drug manipulation habits, perceptions about oral dosage forms and future needs of oral dosage forms for children. This was a qualitative study consisting of focus group discussions with physicians, nurses and clinical pharmacists in a tertiary university hospital with the objective of bringing forward a holistic view on this research topic. These healthcare professionals recognized different administration challenges that were classified as either dosage form-related or patient-related ones. A lack of depot formulations developed especially for children as well as oral pediatric dosage forms of drug substances currently available as intravenous dosage forms was recognized. The preferred oral dosage forms were oral liquids and orodispersible tablets. Patient-centered drug administration practices including factors facilitating drug administration both at hospital wards and at home after patient discharge were identified. Among all healthcare professionals, the efficient cooperation in drug prescribing and administration as well as in educating the child’s caregivers in correct administration techniques before discharge and improving the overall discharge process of patients was emphasized. This study complements the prevalent understanding that new dosage forms for children of varying ages and stages of development are still needed. It also brings a holistic view on different aspects of oral drug administration to pediatric patients and overall patient-centered drug administration practices.